Slip Effects on MHD Squeezing Flow of Jeffrey Nanofluid in Horizontal Channel with Chemical Reaction - Nur Azlina Mat Noor; Sharidan Shafie; Mohd Ariff Admon (Mathematics, 2021)
The heat and mass transfer characteristics on hydromagnetic squeeze flow of Jeffrey nanofluid between two plates over a permeable medium by slip condition with the influences of viscous dissipation and chemical reaction is examined. Buongiorno’s nanofluid model, which includes Brownian motion and thermophoresis impacts, is implemented in this research. The governing nonlinear partial differential equations are transformed to the nonlinear ordinary differential equations via asimilarity transformation. The transformed equations are solved by employing numerical techniques of Keller-box. A comparison of the skin friction coefficient, Nusselt and Sherwood numbers with reported outputs in the journals are carried out to validate the present outputs. An excellent agreement is found. The results show that the squeezing of plates accelerates the velocity and wall shear stress. Furthermore, the velocity, temperature and concentration profile decrease when the Hartmann number and ratio of relaxation and retardation times increases. The raise in thermophoresis and viscous dissipation elevate the temperature profile and the heat transfer rate. Furthermore, the mass transfer rate declines due to the strong Brownian motion in the nanofluid, whereas it increases with the addition of chemical reaction and thermophoresis.